DETERMINANT FACTORS ON THE PREVENTION OF ACCOUNTING FRAUD IN THE LOCAL GOVERNMENT OF MEDAN CITY WITH APPARATUS MORALITY AS A MODERATING VARIABLE - Wanda Annisa Lubis; Erlina; Abdillah Arif Nasution (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This study aims to determine whether good governance, adherence to accounting rules, competence, organizational culture and the role of internal audit affect the prevention of accounting fraud in the Regional Government of Medan City. In addition, this study also aims to determine whether apparatus morality can be used as a moderating variable in this research model. The type of research conducted is causal associative research using a quantitative approach. The location of this research was conducted at all OPD (Regional Apparatus Organization) within the Medan City Regional Government. The sample in this study were 93 Medan City Local Government officials consisting of the Head of the Agency, Secretary and Head of the Finance Section of each OPD. The data used is primary data and the data analysis method used is Partial Least Square (PLS) which is carried out with the help of SmartPLS software. The results of this study indicate that partially good governance, adherence to accounting rules, organizational culture and the role of internal audit are proven to have a positive and significant influence on the prevention of accounting fraud in the Regional Government of Medan City. While competence is proven to have no significant effect on the prevention of accounting fraud in the Regional Government of Medan City. While the results of moderating testing show that the morality of the apparatus is proven to be able to moderate the influence of good governance, adherence to accounting rules, competence and organizational culture on the prevention of accounting fraud in the Regional Government of Medan City.